Inclusion of wheat bran in barley-soybean meal diets with different phosphorus levels for growing-finishing pigs I. Effects on nutrient digestibility and mineral balances in finishing pigs - Helander, Eija; Näsi, Matti; Partanen, Kirsi (Agricultural and Food Science, 1994)
The effect of the intrinsic phytase of wheat bran (WB) on phytin-phosphorus availability to pigs on barley-soybean meal diets was measured in a digestibility and balance experiment using a 2x3 factorial arrangement in a 6x5 cyclic change-over design. The factors were WB inclusion (0 or 100 g per kg, later referred to as WB- and WB+, respectively) and three phosphorus (P) levels: high (HP), medium (MP) and low (LP). The inclusion of WB in the diet did not significantly improve dietary P utilization. However, the absorption and retention of P appeared to be slightly improved by WB inclusion in the LP diet. This improvement may be due to WB phytase. The effects of WB on the digestibility and balance of other minerals remained relatively small. The P level, on the other hand, had a greater effect on mineral balances. Ash digestibility was not affected by the treatments. Dry matter and organic matter digestibilities were impaired when WB was included in the diet. N absorption of intake was higher (p<0.01) on WB+ diets. The retention of N appeared to decrease on HP and MP diets due to WB, but on LP diets no decrease was observed. Regarding the polluting P-emission, the LPWB+ diet appeared to be the most favourable, since the faecal excretion of P was the lowest and the overall retention coefficient of P was the highest. On the basis of these results, an addition of 100 g WB to the diet in order to improve P utilization does not seem very attractive.